Angestellte zwischen Rechts- und Sozialgeschichte: Forschungsfragen zur Entstehung einer Arbeitnehmerkategorie - Thorsten Keiser (Rechtsgeschichte - Legal History, 2022)
The article deals with the development of the law of employees (Angestellte) in Germany. At the beginning of the 20th century, the new category of white-collar workers increasingly became the focus of the legal, economic and social sciences. The article discusses what legal-historical research questions result from this. Central problems of the employment relationship of that time are outlined using source examples from both case law and the contemporary legal literature. It becomes clear that the white-collar workers’ self-image played a major role in the development of the law of employees. In many respects, the latter was characterised by the attempt to demarcate it from that of labourers (Arbeiter), though there were also convergences. Overall, the history of the law of employees is still a blind spot in comparison to the already well-researched history of the law of industrial workers.